2019
DOI: 10.1186/s12915-019-0660-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of skin care products on skin chemistry and microbiome dynamics

Abstract: Background: Use of skin personal care products on a regular basis is nearly ubiquitous, but their effects on molecular and microbial diversity of the skin are unknown. We evaluated the impact of four beauty products (a facial lotion, a moisturizer, a foot powder, and a deodorant) on 11 volunteers over 9 weeks. Results: Mass spectrometry and 16S rRNA inventories of the skin revealed decreases in chemical as well as in bacterial and archaeal diversity on halting deodorant use. Specific compounds from beauty prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
148
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(160 citation statements)
references
References 83 publications
7
148
0
5
Order By: Relevance
“…To transform the biological insights provided by our EAI approach into actionable insights, we ranked the 186 genera by average SHAP impact and report the consensus top impactful genera for our bag of models. Our findings demonstrate the potential of explainable artificial intelligence in contributing to the growing body of knowledge of microbes and their host-interactions, and its future impact in research fields from cosmetic and medical research to forensic science and personal health monitoring (29,33,38,39).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…To transform the biological insights provided by our EAI approach into actionable insights, we ranked the 186 genera by average SHAP impact and report the consensus top impactful genera for our bag of models. Our findings demonstrate the potential of explainable artificial intelligence in contributing to the growing body of knowledge of microbes and their host-interactions, and its future impact in research fields from cosmetic and medical research to forensic science and personal health monitoring (29,33,38,39).…”
Section: Introductionmentioning
confidence: 71%
“…However, there is still a limited understanding of changes in the microbiome associated with cosmetic dry skin. We show that our EAI approach has the potential to provide insights on the effect of skin care and hygiene products on the molecular and microbiome composition of the skin (33).…”
Section: Introductionmentioning
confidence: 97%
“…Collectively, these results suggest that there is some degree of validity to inferring community properties from phylogenetic characterization [33], yet strain level information can be critical to obtaining an accurately detailed profile. In addition, recent work by Bouslimani et al [10] has revealed that skin hygiene products can remain on the skin long after use is discontinued, and these products can influence microbiome composition [11]. Our approach may be used to develop a more detailed understanding of how and why the microbiome shifts in response to the use of certain hygiene and cosmetic products.…”
Section: Discussionmentioning
confidence: 93%
“…We screened a subset of representative, aerobic, isolates for the ability to utilize carbon sources present on the skin surface using tetrazolium dye assays with Lacking from the group are Cutibacterium representatives (formerly Propionibacterim), which play an important role in metabolite processing on the skin [11]. The strains tested utilized a total of 45 out of the 68 carbon compounds examined, which included steroids, fatty acids, sugars, amino acids, and other classes of chemicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation